Analysis of Carbon Trading Potential in Forest Conservation Areas as A Sustainability Strategy in PT Cheil Jedang Indonesia Pasuruan - Ayuni Sabrina Zanuharsih; Muhammad Wildan Affan (PT. Publikasiku Academic Solution, 2025)
Carbon trading is a strategic mechanism to support sustainability in Indonesia by integrating economic, environmental and social considerations. This research explores the potential of carbon trading in the forest conservation area of PT Cheil Jedang Indonesia (CJI) Pasuruan as a sustainability strategy to maximize economic and ecological benefits. This research used a qualitative approach with data collection through observation and documentation. Primary data was obtained from stakeholders, while secondary data included reports, regulations and literature. Analysis was conducted by combining economic valuation and qualitative descriptive analysis. PT CJI Pasuruan demonstrated significant carbon trading potential through two conservation areas, namely Patuguran Mangrove and Puspo area, with an estimated economic value of carbon reaching IDR 4,147,929,778. In addition, the company is committed to reducing greenhouse gas emissions and supporting sustainable forest management practices. The results indicate that carbon trading can contribute to economic, environmental and social sustainability. Despite challenges such as regulatory complexity, this initiative can serve as a model for other companies looking to implement sustainability-based strategies.